The digital transformation of auditing and the evolution of the internal audit - Daidj, Nabyla, 1964- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The main objective of this book is to provide both academics and practitioners with a global vision of the evolution of internal auditing in a fast-changing business landscape driven by digital transformation. Digital transformation has been first associated with the emergence and the development of new technologies (artificial intelligence, blockchain, cloud computing, data analytics, predictive analytics, robotic process automation, IOT, drones etc.). Beyond the technological dimensions, this transformation has several impacts on businesses, organizations and processes and raises several questions for auditing activities. This book explores how digitalization not only has an impact on the audit environment, but also on internal audit practices and methodologies, information technology (IT)/information system (IS) audit, IT governance and risk management. The auditing profession also has to face the same challenges. Auditors should develop new skills. To continue to provide high quality service in such an environment, the methodologies, the process and the tools used for conducting an audit have progressively changed from those applied to the traditional audit. The internal audit has gradually moved from a monitoring - passive function - to a strategic and dynamic function in organization. Finally, the book also investigates the impact of the COVID-19 pandemic on internal auditing. The author highlights the need for a new vision and renewed forecasting tools. The post-COVID 19 business and corporate world has changed. Internal audit, as a key strategic function, must evolve too"--
Keywords: Auditing, Internal; Auditing -- Technological innovations; BUSINESS & ECONOMICS / Auditing; BUSINESS & ECONOMICS / Accounting / Financial